Proceso caritas y calidad de vida post histerectomía. - Heredia Amaguaya, Esthela Pilar (2024)
The application of the Caritas process, based on Jean Watson's theory, focuses on humanitarian, transpersonal, loving, holistic and compassionate care, promoting healing and integral well-being. The objective of this research work is to analyze the aspects related to patient care and the application of the Caritas process in the quality of life of post-hysterectomized women. The hysterectomy procedure is a common surgical intervention that consists of the removal of the uterus. This can lead to significant changes that cause physical, emotional and psychological impacts on patients. Therefore, through an exhaustive documentary review, the concept of transpersonal care and the philosophical foundation of care are analyzed, analyzing how these can be applied to improve postoperative quality of life, identifying effective nursing interventions to satisfy needs, reduce, alleviate changes and promote comprehensive recovery through humanized care, seeking psychological, emotional, and spiritual well-being, which includes family participation. To this end, a systematic search was carried out for documents with updated information with scientific support in different electronic databases of regional and global impact such as: Scielo, Elsevier, Google Scholar, Scopus, PubMed, web pages: National Library of Medicine, World Organization of Health (WHO), Sage Journals Virtual health library, BENNESSERE, among others. Key words were used to search for information, hysterectomy, process, care, nursing, quality of life, hysterectomy. The results obtained suggest that the implementation of Watson's caritas process in postoperative care by nursing can positively contribute to improving the quality of life of women, relieving emotional stress and anxiety, encouraging selfcare, strengthening support. family emotional, promoting the empowerment of the patient to achieve physical, emotional and spiritual healing, contributing to general well-being. This approach not only improves the experience of patients but can also serve as a model for nursing practice in similar contexts, promoting their professional training, encouraging multidisciplinary teamwork.